Therapeutic properties of multi-cannabinoid treatment strategies for Alzheimer’s disease - Coles, Madilyn; Steiner-Lim, Genevieve Z.; Karl, Tim (Frontiers in Neuroscience, 2022)
Alzheimer’s disease (AD) is a debilitating neurodegenerative disease characterised by declining cognition and behavioural impairment, and hallmarked by extracellular amyloid-β plaques, intracellular neurofibrillary tangles (NFT), oxidative stress, neuroinflammation, and neurodegeneration. There is currently no cure for AD and approved treatments do not halt or slow disease progression, highlighting the need for novel therapeutic strategies. Importantly, the endocannabinoid system (ECS) is affected in AD. Phytocannabinoids, including cannabidiol (CBD) and Δ9-tetrahydrocannabinol (THC), interact with the ECS, have anti-inflammatory, anti-oxidant, and neuroprotective properties, can ameliorate amyloid- and NFT-related pathologies, and promote neurogenesis. Thus, in recent years, purified CBD and THC have been evaluated for their therapeutic potential. CBD reversed and prevented the development of cognitive deficits in AD rodent models, and low-dose THC improved cognition in ageing mice. Importantly, CBD, THC, and other phytochemicals present in the Cannabis sativa plant interact with each other in a synergistic fashion (called the entourage effect) and have greater therapeutic potential when administered together rather than individually. Thus, treatment of AD using a multi-cannabinoid strategy (such as whole plant cannabis extracts or particular CBD:THC combinations) may be more efficacious compared to cannabinoid isolate treatment strategies. Here, we review the current evidence for the validity of using multi-cannabinoid formulations for AD therapy. We discuss that such treatment strategies appear valid for AD therapy but further investigations, particularly clinical studies, are required to determine optimal dose and ratio of cannabinoids for superior effectiveness and limiting potential side effects. Furthermore, it will be pertinent that future investigations consider sex effects.